Solve using the Square Root Property 2x+4=12x-6

Math
2x+4=12x-6
Move all terms containing x to the left side of the equation.
Tap for more steps…
Subtract 12x from both sides of the equation.
2x+4-12x=-6
Subtract 12x from 2x.
-10x+4=-6
-10x+4=-6
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Subtract 4 from both sides of the equation.
-10x=-6-4
Subtract 4 from -6.
-10x=-10
-10x=-10
Divide each term by -10 and simplify.
Tap for more steps…
Divide each term in -10x=-10 by -10.
-10x-10=-10-10
Cancel the common factor of -10.
Tap for more steps…
Cancel the common factor.
-10x-10=-10-10
Divide x by 1.
x=-10-10
x=-10-10
Divide -10 by -10.
x=1
x=1
Solve using the Square Root Property 2x+4=12x-6

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top